Strategi Peningkatan Investasi Di Provinsi Nusa Tenggara Barat - Arifudin (Journal of Resources and Reserves (JRR), 2023)
In order to identify and solve regional investment problems and synergize them with national strategies, it is necessary to develop a policy framework to create conducive conditions for investment in the NTB Province. The aim of this research is to determine the potential, opportunities and investment factors in West Nusa Tenggara Province as well as the government's efforts in developing investment in West Nusa Tenggara Province. The population in this study was 39 people with a sample of 17 respondents consisting of parties directly related to investment issues in NTB Province consisting of Government Apparatus (BAPPEDA for Economic Sector, Investment and One-Stop Integrated Services Service, and Regional Secretariat. Economy) as well as from the Employers' Association (KADIN and Investors/Entrepreneurs). Sample determination was carried out using the purposive quota sampling method. These research variables are in accordance with those used by KPPOD in its research regarding regional investment attractiveness in 2019, namely including institutional, social political, regional economic, labor and physical infrastructure variables. The analytical tool used is AHP (Analytical Hierarchy Process). Based on research results, investment potential and opportunities in NTB Province are in the agricultural sector, trade, hotel and restaurant sector, processing industry sector, and services sector. Meanwhile, the determinant of investment attractiveness that has the greatest weight is institutional factors with a weight of 34.1%, followed by socio-political factors at 17.3%. In third place is the labor factor with a weight of 16.6% and in fourth place is the physical infrastructure factor at 16.2%. Lastly is the regional economic factor with a weight of 15.8%.